Challenges of AI Technologies Chat GPT in Practicing Education of students in the UAE - Alfalahi, Buti Obaid Saeed; Lamdjad, Imane; Alnujaifii, Mustafa (Journal of Posthumanism, 2025)
Artificial Intelligence (AI) Chat CPT is becoming pervasive. The technology is reaching into so many facets of sectors fundamental element reshaping, particularly education. This caused difficulties and challenges .The research aims to discuss opportunities and challenges that AI in education of children and provide a comprehensive view of these technologies.In this research, the research utilized method The descriptive, analytical and inductive method .the finding of this research that many challenges of education such as security Data privacy,stupidity mind of students.,impede skills such as creativity of children and critical thinking,The research recommended cooperation between Various stakeholders, including government agencies and educational institutions, and educators should push for the utilization of AI’s vast applications in the educational sector.